Exploring DIY Urbanism: Housewives’ Participation in Recycling Used Cooking Oil for Candle Making in Tangerang, Indonesia - An Nisaa, Ranti, Ms.; Rahayu, Dewi Pudji, Ms.; Lestari, Suci, Ms. (UI Scholars Hub, 2023)
This study explores the do-it-yourself (DIY) project in an urban context, a candle making with recycled used cooking oil (UCO), aiming to empower housewives in Gaga Village, Tangerang, Indonesia. UCO, a household waste material, becomes a trigger for this project because it pollutes the environment and reduces soil fertility if discarded unresponsible. In this scenario, involving the participation of urban housewives can be a way to address this issue. Urban housewives have spare time between their daily activities and present great potential in such a project. Recycling UCO for candle- making material arguably can increase the family’s economic capacity and, at the same time, reduce environmental pollution. This project, which involved four stages— preparation, implementation, monitoring, and evaluation—is assessed to examine the response of the participating housewives. The assessment employed a qualitative study, examining the project based on pre- and post-test conditions. The results show an increase in knowledge of UCO by 81.1%, utilization of UCO by 82.1%, understanding of making UCO candles by 39.3%, and understanding of economic opportunities from making UCO candles by 80.9%. Even though the DIY activity is highly interesting for housewives, 78.6% still do not know whether candle-making can be considered an economic opportunity. Through this program, other productive and creative DIY activities can also be identified that can be an extra income for their families without leaving the house. It can be concluded that further intensive and interactive training is necessary to empower housewives with further potential economic opportunities.